Dragging the chain: anchor scour impacts from high-tonnage commercial vessels on a soft bottom macrobenthic assemblage - Davis, Andrew R.; Broad, Allison; Steele, Chantel; Woods, Caitlin; Przeslawki, Rachel; Nicholas, W. A. (Tony); Maher, William; Krikowa, Frank; Morris, Bradley; Ingleton, Timothy C.; O’Hea Miller, Sarah; Rees, Matthew J. (Frontiers in Conservation Science, 2025)
International shipping is the backbone of the global economy with 80% of the world’s trade (by volume) transported by ship. The potential environmental impacts of this multi-billion-dollar industry have received considerable attention, particularly emissions into air and sea. Many of these large commercial vessels lay at anchor for extended periods while awaiting their turn to enter port, and yet the impacts associated with anchoring remain virtually unexamined. Anchors can exceed 20 tonnes, with chains up to hundreds of metres in length and individual links weighing up to 200kg; there is potential for significant effects on seafloor biota where anchoring is concentrated. Filling knowledge gaps in deep-water wave-exposed environments is logistically challenging and expensive. To do so we used sediment grabs collected offshore from the Port of Newcastle (SE Australia) – the world’s largest coal export terminal – to sample infaunal assemblages in anchor-affected locations relative to reference locations (30 to 55m water depth). Polychaetes and crustaceans were the most abundant biota in the samples ( 85%), whereas molluscs were very low in abundance (<3%), despite being well represented in terms of diversity (11 families of bivalves and 9 families of gastropods). Invertebrate abundance almost doubled in areas exposed to anchoring compared to reference areas. In contrast, invertebrate diversity declined with increasing anchoring activity, however this relationship was weak. Importantly, we observed major shifts in the overall invertebrate assemblage at anchored-affected locations – with reductions in suspension feeders mirrored by increases in scavengers and predators. We assert that suspension feeders were negatively impacted by sediment mobilisation or direct physical damage from anchor chains, while opportunistic scavengers and mobile predators benefitted from this disturbance. We contend that anchor disturbance is a global issue given burgeoning marine trade. Data on the effects of anchoring are urgently required to better inform the management of environments regularly used as anchorages.